Genetic variance and covariance compenents for feed intake, average daily gain, and postweaning gain and indices to improve feed efficiency in growing beef cattle - Retallick, Kelli June (Kansas State University, 2015)
Feed is the single most expensive cost related to beef cattle production. Currently a 70 d performance test is recommended for accurate calculation of efficiency. Previous research has suggested intake tests can be limited to 35 d. Objectives of this study were to estimate genetic parameters for growth and intake traits, compare two alternative indices for feed efficiency, and quantify the genetic response to selection for feed efficiency combining an intake test with two types of gain data. On–test average daily feed intake (ADFI), on-test average daily gain (ADG), and postweaning gain (PWG) records on 5,606 growing steers and heifers were obtained from the U.S. Meat Animal Research Center in Clay Center, NE. On-test ADFI and ADG data were collected from a minimum of 62 to 148 d testing days. Independent quadratic regressions were fitted for body weight on time, and on-test ADG was predicted from the resulting equations. PWG was calculated by subtracting adjusted 205-d weights from 365-d weights and dividing by 160. Genetic correlations were estimated using multiple trait animal mixed models with ADG, ADFI, and PWG for both sexes as dependent variables. The genetic correlations between ADG and PWG for both steers (0.81) and heifers (0.65) were strong. This indicates PWG is a strong proxy for ADG on-test and long test periods may not be necessary. Indices combining EBVs for ADFI and ADG and for ADFI and PWG were evaluated. For each index, the weighting of gain was arbitrarily set to 1.0 and the weighting for ADFI was the negative of the average of the intra-contemporary group ratio of mean gain divided by mean ADFI. Values were combined with EBV to compute two index values per animal. Pearson correlations for steers (0.96) and heifers (0.45) indicated a strong relationship for steers between the indices. Because more animals can be measured for intake, using PWG increases genetic progress of selection for feed efficiency by 15-17% per year. These findings support using PWG data in combination with ADFI to determine efficient animals, lessen costs, and increase annual feed efficiency genetic change.
Keywords: Feed efficiency; Postweaning gain; Beef cattle; Animal Sciences (0475)